2018
DOI: 10.1080/17461391.2018.1442500
|View full text |Cite
|
Sign up to set email alerts
|

Women show similar central and peripheral fatigue to men after half‐marathon*

Abstract: Women are known to be less fatigable than men in single-joint exercises, but fatigue induced by running has not been well understood. Here we investigated sex differences in central and peripheral fatigue and in rate of force development (RFD) in the knee extensors after a half-marathon run. Ten male and eight female amateur runners (aged 25-50 years) were evaluated before and immediately after a half-marathon race. Knee extensors forces were obtained under voluntary and electrically evoked isometric contracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 66 publications
5
18
0
Order By: Relevance
“…While in the present study the same relative speed (≈78% of MAS) was observed in both groups, men completed the 21-km faster than women due to their higher MAS. For both groups, the observed performance was in the range of expected values for half-marathon participants of similar training levels (e.g., [ 51 ]). The longer exercise duration for women resulted in a similar weight loss (that could be used as a rough estimation of hydration status), which was in the range of typical weight loss observed with a half-marathon race [ 31 ].…”
Section: Discussionsupporting
confidence: 57%
“…While in the present study the same relative speed (≈78% of MAS) was observed in both groups, men completed the 21-km faster than women due to their higher MAS. For both groups, the observed performance was in the range of expected values for half-marathon participants of similar training levels (e.g., [ 51 ]). The longer exercise duration for women resulted in a similar weight loss (that could be used as a rough estimation of hydration status), which was in the range of typical weight loss observed with a half-marathon race [ 31 ].…”
Section: Discussionsupporting
confidence: 57%
“…Shortly after the half-marathon, the maximal force decreased by ≈21%, confirming that the prolonged run induced moderate muscle fatigue in knee extensors. This is in line with our previous studies where we also found a moderate decrease (ranged 11–24%) in maximal force after half-marathons performed in similar experimental conditions ( Boccia et al, 2017a , b , 2018 ). The strength loss is a common finding after endurance running in ecological race conditions: it increases non-linearly with the duration of exercises and it may vary between 8 and 41% ( Millet and Lepers, 2004 ; Place et al, 2010 ; Giandolini et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…The amount of central fatigue depends on many exercise parameters, such as intensity, duration, and contraction modality, among others ( Taylor et al, 2016 ). While a detailed discussion of the mechanisms regulating the amount of central fatigue is beyond the scope of this paper, it is evident in the literature that central fatigue is overall greater for extreme-duration running ( Millet and Lepers, 2004 ; Martin et al, 2010 ; Temesi et al, 2014 ) rather than for shorter, more intense bouts like half-marathons ( Ross et al, 2010 ; Boccia et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations